2019
DOI: 10.1002/pip.3119
|View full text |Cite
|
Sign up to set email alerts
|

Rapid thermal processing of cost‐effective contacts for silicon solar cells

Abstract: This paper reports on the investigation of rapid thermal processing (RTP) of contacting the Al‐BSF solar cell with Ag, Cu, and Ni in conjunction with aerosol printing technique. The study showed a liftoff and delamination, respectively, for the bi and tri stack layers of Ag frit/Ni and Ag frit/Ni/Cu fired above 790°C peak firing temperature. The 770°C peak firing temperature gave excellent electrical performance for both bi and tri stack layer contacts, which is not favorable to forming thick back surface fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…This occurrence could stem from multiple factors, including differential thermal expansion, interfacial reactions, and inadequate surface preparation, among others. These observations align with previous study [25], which reported similar lift-off and delamination issues in aerosol printed bi and tri stack layers of Ag frit/Ni and Ag frit/Ni/Cu when fired above 790°C peak firing temperature. The efficiency and series resistance parameters, plotted based on finger width associated with lift-off and delamination in stacked contacts, are presented in Fig.…”
Section: Resultssupporting
confidence: 92%
“…This occurrence could stem from multiple factors, including differential thermal expansion, interfacial reactions, and inadequate surface preparation, among others. These observations align with previous study [25], which reported similar lift-off and delamination issues in aerosol printed bi and tri stack layers of Ag frit/Ni and Ag frit/Ni/Cu when fired above 790°C peak firing temperature. The efficiency and series resistance parameters, plotted based on finger width associated with lift-off and delamination in stacked contacts, are presented in Fig.…”
Section: Resultssupporting
confidence: 92%
“…This occurrence could stem from multiple factors, including differential thermal expansion, interfacial reactions, and inadequate surface preparation, among others. These observations align with a previous study, 26 which reported similar lift‐off and delamination issues in aerosol printed bi‐ and tri‐stack layers of Ag frit/Ni and Ag frit/Ni/Cu when fired above 790°C peak firing temperature.…”
Section: Resultssupporting
confidence: 92%